2023
DOI: 10.3390/land12091716
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Aging Population in Rural Families on Farmers’ Willingness to Withdraw from Homesteads in Shenyang, Liaoning Province, China

Hanlong Gu,
Yuqing He,
Bingyi Wang
et al.

Abstract: Population aging presents a significant global challenge. In China, the aging of the rural population coincides with inefficient rural homestead utilization. While the Chinese government has enacted policies to address this, their impact remains limited. Utilizing survey data from 403 rural families in Shenyang, Liaoning Province, China, this study applies the binary Logit and mediating effect models to analyze the impact of rural family population aging on farmers’ willingness to withdraw from homesteads with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Scholars have paid attention to the factors affecting the willingness to withdraw from the homestead. The most common methods used by scholars are the logit model [14], probit model [15], mediation effect model [16], and moderating effect model [17]. The research mainly focuses on individual and household characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have paid attention to the factors affecting the willingness to withdraw from the homestead. The most common methods used by scholars are the logit model [14], probit model [15], mediation effect model [16], and moderating effect model [17]. The research mainly focuses on individual and household characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Data from the seventh national census show that the proportion of the Chinese population aged 60 and above has increased from 5.44% in 2010 to 18.70% in 2020. In addition, as a large number of young and strong rural laborers flock to cities and non-agricultural sectors, the age structure of the agricultural labor force is aging [17], the level of human capital is low, and there is an increasing lack of effective labor force [18], resulting in the problem of population aging in China's rural areas and agricultural sectors becoming even more pronounced [19][20][21][22][23]. The 2015 National 1% Population Sampling Survey found that from 1982 to 2015, China's rural population over 60 years old increased by 2.37 times [24].…”
Section: Introductionmentioning
confidence: 99%